Urban Subnature and Dirt. On Poetry by Władysław Sebyła - Kokoszka, Magdalena (Porównania, 2024)
The protagonist of this article is urban subnature, as seen through the eyes of the interwar poet Władysław Sebyła. Subnatural forms of life, such as invasive species or entire ecosystems existing in urban puddles, in soot, and in dust, are a natural reality that seems interesting as an overlooked part of the natural history of cities—a history dominated by aesthetic perceptions. Due to hygienic and aesthetic ideas, the presence of subnature in urban space was considered a sign of civilizational backwardness. The author of Pieśń Sczurołapa (The Song of the Ratcatcher) shared with his epoch the dream of “glass houses in fertile orchards”, which may be why he proved particularly sensitive to subnature. In this article, he is shown as a poet whose sensitivity and imagination were shaped at the beginning of the twentieth century by landscapes such as the “factory of nature” in Kłobuck—a marshy, muddy meadow located by a water mill—(a pre-modern world of renewable resources) and the mining and industrial areas of the Dąbrowa Coal Basin and Upper Silesia (a modern world of intensive exploitation of nature).